2018
DOI: 10.3390/met8121027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al Content on the Inclusion-Microstructure Relationship in the Heat-Affected Zone of a Steel Plate with Mg Deoxidation after High-Heat-Input Welding

Abstract: The effects of Al content on inclusions, microstructures, and heat-affected zone (HAZ) toughness in a steel plate with Mg deoxidation have been investigated by using simulated high-heat-input welding and an automated feature system. The studies indicated that the main kind of oxysulfide complex inclusions in two steels without and with Al addition were both MgO-MnS. The number densities and mean sizes of inclusions were 96.65 mm−2 and 3.47 μm, 95.03 mm−2 and 2.03 μm, respectively. The morphologies of MgO-MnS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…According to the SEM–EDS mapping results, the inclusion is identified to be MgO·Al 2 O 3 ·TiN·MnS inclusion with the diameter of about 2 μm. It is therefore demonstrated that the Mg containing complex inclusions with the size above 1 μm can effectively promote the nucleation and growth of intragranular ferrite, which is consistent with the results of our previous researches, [ 29,32,55,56 ] so as to prevent the generation of transverse corner cracks. In addition, the formed complex inclusions of the Mg containing oxides+(Ca, Mn)S, (Mg, Mn)S, or (Mg, Ca, Mn)S can also reduce the harmfulness of the extended MnS [ 57 ] to improve the transverse impact toughness of steel plate.…”
Section: Resultssupporting
confidence: 90%
“…According to the SEM–EDS mapping results, the inclusion is identified to be MgO·Al 2 O 3 ·TiN·MnS inclusion with the diameter of about 2 μm. It is therefore demonstrated that the Mg containing complex inclusions with the size above 1 μm can effectively promote the nucleation and growth of intragranular ferrite, which is consistent with the results of our previous researches, [ 29,32,55,56 ] so as to prevent the generation of transverse corner cracks. In addition, the formed complex inclusions of the Mg containing oxides+(Ca, Mn)S, (Mg, Mn)S, or (Mg, Ca, Mn)S can also reduce the harmfulness of the extended MnS [ 57 ] to improve the transverse impact toughness of steel plate.…”
Section: Resultssupporting
confidence: 90%
“…Nowadays, oxide metallurgy technology has been considered as an effective method to improve the heat-affected zone (HAZ) toughness of steel plates after high-heat-input welding [2][3][4]. The oxide metallurgy technology is to make use of oxide particles or other kinds of inclusions and precipitate particles as the nucleation sites of intragranular acicular ferrite (IAF), or for pinning the growth of austenite grain in HAZ of steel plate during the welding process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microstructures in 0Al show observably more favourable to the HAZ toughness than those in 200Al. In our previous study [20], the influence of Al content on the micron inclusion-microstructure relationship in the two investigated steels has been described in detail. It was stated that IAFs are nucleated by the MgO-MnS complex inclusions in the Mg-deoxidized steel without Al, while the MgO-MnS complex inclusions with different morphologies in the Mg-deoxidized steel containing 0.02 wt-% Al hardly nucleate to IAFs.…”
Section: Prior Austenite Grain Size and Microstructuresmentioning
confidence: 99%